Aspiration of a cockroach - Albert Bousso; Iracema de Cassia Oliveira Fernandes; Ricardo Yamaguchi; Lincoln Andrade; José Carlos Fernandes (Einstein (São Paulo), 2008)
It is described a five-month-old infant admitted to our pediatricintensive care unit who aspirated a cockroach. The cockroach wasremoved through bronchoscopy. The child arrived at the emergencyroom in cardiopulmonary arrest and despite full respiratory andcardiovascular support was discharged with evidence of severeneurological sequelae. It is known that this is the first case of acockroach aspiration in a five-month-old infant and reinforces thataspiration of an insect must be considered a possibility in patientswith an unidentified organic foreign body aspiration.